Wildlife Science : Connecting Research with Management. - Sands, Joseph P. (CRC Press, 2012)
Despite the potential synergy that can result from basing management applications on results from research, there is a polarization of cultures between wildlife managers and wildlife researchers. Wildlife Science: Connecting Research with Management provides strategies for bridging cultural and communication gaps between these groups Contributors present case studies highlighting the role of state and federal agencies and private organizations in management and research; the lingering disconnects between grassland birds, quail, and deer research and management; as well as the development of ma.